Henry Bibb’s (Dis)claiming Family: Malinda as a Case Study of Black Women’s Symbolic Annihilation in Antebellum Literature - Asmaa Alshehri (American and British Studies Annual)
Existing scholarship on the autobiography Narrative of the Life and Adventures of Henry Bibb prioritizes Bibb’s masculinity and the impact of slavery on Black families, often overlooking the complex experiences of enslaved Black women such as Bibb’s first wife Malinda within such a narrative. Amy Lewis’s article “Who’ll Speak for Malinda?” distinguishes itself by offering an alternative narrative focusing on Malinda’s experience. My paper builds on Lewis’s work by arguing that despite condemning slavery, Bibb’s narrative inadvertently perpetuates Malinda’s symbolic annihilation. Through a close reading of Bibb, my study attempts to reveal how enslaved women’s experiences are often omitted, trivialized, and condemned in American antebellum literature. By devoting particular attention to the “symbolic annihilation” of enslaved women, this paper responds to Amy Lewis’s call for alternate narratives and offers a critical shift in reading and interpreting depiction and omission of Black women in ex-enslaved narratives throughout nineteenth-century antebellum America. This approach has the potential to uncover the complex realities of Black women to offer valuable insights into their lives and experiences, thus challenging dominant interpretations of slave narratives.